New biomarkers in cancers - Novak, Daniel; Utikal, Jochen (Cancers, 2021)
In this Special Issue of Cancers, the latest insights on biomarkers in cancers are presented in 33 up-to-the-minute research papers and reviews summing up the tremendous progress in this interesting and important field of research [...]